Assessment of Household Solid Waste Composition and Characterization for Sustainable Waste Management in Ba Ria–Vung Tau Province, Vietnam - Thanh, Dang My; Duc, Pham Anh; Hiep, Bui Tat (Journal of Sustainability and Environmental Management, 2024)
Classifying household solid waste into specific categories was a foundational step for effective waste management, enabling tailored strategies for each waste type. The household solid waste in Ba Ria–Vung Tau Province was classified into three main categories: (i) food waste, (ii) reusable and recyclable waste, and (iii) inorganic and hazardous waste—each requires distinct handling, processing, and disposal methods to optimize resource use and minimize environmental impact. The physical properties of solid waste have been characterized based on the density of waste, moisture content, and calorific value. The components of household solid waste in Ba Ria–Vung Tau Province recorded urban areas, rural areas, and islands in the percentage by dry weight. According to the surveyed results in 2021 – 2022, the household solid waste generated in Ba Ria–Vung Tau Province was 1,288,180 kg/day. Of which, the quantity of solid waste generated in urban areas was highest with 860,740 kg/day, next in rural areas at 418,600 kg/day, and the district of Con Dao Island at 8,840 kg/day. The values of the various parameters were recorded: density (292.5 – 349.1 kg/m3), moisture content (54.3 – 61.2 %), and calorific value (6.37 – 9.28 MJ/kg). The high calorific value of waste indicates that it contains a significant amount of energy that could be harnessed. According to statistics, the amount of household solid waste generated in this province by 2030 will be more than 2,458,000 kg/day. This study is the baseline for a sustainable waste management system with a focus on source separation.